Colorectal Cancer Causes and Treatments - Nasrallah, Anita (2014)
Colon cancer is the cancer of the epithelial cells lining the colon. This type of cancer occurs in many people that are either genetically predisposed or exposed to risk factors. Colorectal cancer is mainly divided into different stages according to invasiveness and metastatic ability of the tumor. Many mutations are acquired, leading to this malignancy. Treatment of colorectal cancer range from surgery in early stages to palliative care in most advanced stages. In this minireview, we summarize the latest findings on colorectal cancer.